Concurrent projects in control laboratorial classes - Soares, Filomena (2015)
This paper presents a laboratorial curricular unit program running in the 1st semester, 4th year of the Integrated Master in Industrial Electronics at the University of Minho. In Project I curricular unit, students designed, developed and implemented an inverted pendulum platform where different control algorithms were tested. Project specifications were formulated by the teachers and students were allowed to conceive different solutions. Some of the final platforms, as well as the perspectives of the students regarding this learning approach, are presented.